Reward system neurodynamics during menstrual pain modulated by COMT Val158Met polymorphisms - Hsu, Pei-Shan; Liu, Ching-Hsiung; Yang, Ching-Ju; Lee, Lin-Chien; Li, Wei-Chi; Chao, Hsiang-Tai; Lin, Ming-Wei; Chen, Li-Fen; Hsieh, Jen-Chuen (Frontiers in Molecular Neuroscience, 2024)
IntroductionPrimary dysmenorrhea (PDM), characterized by cyclic pain, may involve pain modulation within the reward system (RS). The Catechol-O-methyltransferase (COMT) Val158Met polymorphism, which significantly influences dopamine activity, is linked to the regulation of both acute and chronic pain. This study examines the differential neurodynamic modulation in the RS associated with COMT Val158Met polymorphisms during menstrual pain among PDM subjects.MethodNinety-one PDM subjects underwent resting-state fMRI during menstruation and were genotyped for COMT Val158Met polymorphisms. The amplitude of low-frequency fluctuation (ALFF) and functional connectivity (FC) analyses were used to assess the RS response. Psychological evaluations included the McGill Pain Questionnaire, Pain Catastrophizing Scale, Beck Anxiety Inventory, and Beck Depression Inventory.ResultVal/Val homozygotes (n = 50) and Met carriers (n = 41) showed no significant differences in McGill Pain Questionnaire, Beck Anxiety Inventory, and Beck Depression Inventory. However, Met carriers exhibited lower scores on the Pain Catastrophizing Scale. Distinct FC patterns was observed between Val/Val homozygotes and Met carriers, specifically between the nucleus accumbens (NAc) and prefrontal cortex, NAc and inferior parietal lobe, ventral tegmental area (VTA) and prefrontal cortex, VTA and precentral gyrus, and VTA and superior parietal lobe. Only Met carriers showed significant correlations between ALFF and FC values of the NAc and VTA with pain-related metrics (McGill Pain Questionnaire and Pain Catastrophizing Scale scores). NAc ALFF and NAc-prefrontal cortex FC values positively correlated with pain-related metrics, while VTA ALFF and VTA-prefrontal cortex and VTA-superior parietal lobe FC values negatively correlated with pain-related metrics.DiscussionThis study reveals that the COMT Val158Met polymorphism results in genotype-specific functional changes in the brain’s RS during menstrual pain. In Met carriers, engagement of these regions is potentially linked to motivational reward-seeking and top-down modulation. This polymorphism likely influences the RS’s responses, significantly contributing to individual differences in pain regulation.